Protective factors for preventing the use of drugs in the families of a Colombia locality (Revista Latino-Americana de Enfermagem, 2010)
The aim of this study was to analyze the protective factors that prevent drug use in the families of children who attend Community Homes of Family Well-being in a small Colombian locality. This was a quantitative, descriptive, transversal study, with 256 families constituting the sample. Data were collected through a self-applied questionnaire throughout March and April 2007. Protective factors found included demonstrations of affection toward the children, playing with them and talking to them about things they like, open communication, decision making as a couple, flexibility of the nursing process, and establishment of rules. However, some risk factors were also found, such as consumption of legal drugs such as cigarettes and alcohol, and in a low percentage, consumption of illicit drugs. A high percentage of families consider that drug use must be prevented in the first years of life, by the parents. The protective factors found require reinforcement as they are not very strong, and the risk factors must be controlled to turn them into protective factors.